Age-related changes to the neural correlates of working memory which emerge after midlife - Macpherson, Helen N.; White, David J.; Ellis, Kathryn A.; Stough, Con; Camfield, David; Silberstein, Richard; Pipingas, Andrew (Frontiers in Aging Neuroscience, 2014)
Previous research has indicated that the neural processes which underlie working memory change with age. Both age-related increases and decreases to cortical activity have been reported. This study investigated which stages of working memory are most vulnerable to age-related changes after midlife. To do this we examined age-differences in the 13Hz steady state visually evoked potential (SSVEP) associated with a spatial working memory delayed response task. Participants were 130 healthy adults separated into a midlife (40 to 60 years) and an older group (61 to 82 years). Relative to the midlife group, older adults demonstrated greater bilateral frontal activity during encoding and this pattern of activity was related to better working memory performance. In contrast, evidence of age-related under activation was identified over left frontal regions during retrieval. Findings from this study suggest that after midlife, under-activation of frontal regions during retrieval contributes to age-related decline in working memory performance.